Pengaruh Stressing Terhadap Percepatan Pembentukan Gubal Gaharu Pada Tanaman Gaharu (Aquilaria malaccencis, Lamk) - Agus Winarsih; Fifi Puspita; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Agarwood is an aromatic substance formed as brown clumps, blackish brown in the lining of agarwood, divided into 3 classses; agar, kemedangan, ash. Aqualaria malaccencis has been known as an agar producing tree. Naturally, the forming of agar needs teens years. Several method has been known formed agar through wounded to Aquilaria malaccencis, Lamk. The reseach aimed was to test stressing at Aquilaria malaccencis. Lamk in forming agarwood. This research was conducted at Plot Forest Research Institute of Technology Fibers Forest at Ujungbatu, Rokan Hulu, Riau for about 5 months, started from June to October 2011. Aquilaria malaccencis, Lamk, was wound by given fisics stressing consist of without stressing (P0), cordage with 1 ring (P1), cordage with 2 rings (P2), prunning 2/3 part crown (P3), and prunning 1/2 part crown (P4) then combined with biological stressing by inoculation of Fusarium sp. The stressing was designed by randomized block design Duncan’s Multiple Range Test at significant level of 5% was applied to compared physics to agarwood producing. The changed of color and fragrance were analyzed by Non-Parametric Test. Kruskal Wallis at significant level of 5% was applied to evaluate significant treatments. Correlations Test was done between treatment at significant level of 1%. The result showed that Aquilaria malaccencis, Lamk, with fisics tressing (P1, P2, P3, dan P4) showed wood colour changed after 1 month inoculation of Fusarium sp. Stressing cordage with 2 rings (P2) which followed by inoculation of Fusarium sp at Aquilaria malaccencis, Lamk, resulted 26,76 g dryweight of brown agar with best fragrance at level 2 after 5 months stressing. Based on statistical analysis, there were significant between stressing and agar formed. The best stressing at Aquilaria malaccencis, Lamk, was cordage with 2 rings. The result of correlations test showed strong to very strong of infection area, color changing, fragrans and dryweight of agarwood Key words: Aquilaria malaccencis, Lamk., agarwood, stressing